Distribution patterns of gross primary production of mangrove ecosystems in Hainan Island and their driving mechanisms - ZHENG Yinqi1,2,3, SHI Xian3,4, CHEN Quan3,5, WU Lan3,5, CUI Wei6, WANG Wenmei1,2, SUN Zhongyi3,5*, TAN Ke7* (Guangxi Zhiwu)
Mangrove forests, characterized by high photosynthetic rate and low light compensation point, exhibit high gross primary production (GPP), an important component of “blue carbon”. Accurate estimation of regional GPP and quantification of its limiting factors are greatly significant for China to achieve its carbon peaking and carbon neutrality goals. In this paper, the GPP of mangrove ecosystems in Hainan Island from 2016 to 2020 were estimated based on the mangrove vegetation photosynthesis-light use efficiency (MVP-LUE) model using Sentinel-2 imagery and environmental data, and the spatiotemporal distribution pattern of GPP and its driving mechanism were explored. The results were as follows: (1) During the study period, the annual GPP of mangrove ecosystems on Hainan Island showed an increasing trend, with higher GPP in the eastern regions than western regions, and northern regions than southern regions. The mangroves distributed over a large area in northeastern Hainan Island dominate the temporal variation patterns at the whole island scale. However, distinct differences exist in the temporal dynamics across different regions of the mangrove ecosystem in Hainan Island. (2) In terms of the formation mechanism, the spatiotemporal distribution pattern of GPP of mangrove ecosystems on Hainan Island was driven by a combination of multiple meteorological factors. Seasonally within each year, during the transition from the dry season to rainy season, GPP was higher due to lower limitation from air temperature (T air), and the promoting effects of photosynthetically active radiation (PAR) and sea surface temperature. In the middle of the dry season, low T air imposed a serious limitation on GPP, but this T air limitation was weakened with decreasing latitude. In the rainy season, higher cloud cover resulted in PAR becoming a limiting factor for GPP. At the end of the paper, we discussed the uncertainties and limitations of MVP-LUE, and the spatiotemporal distribution patterns of mangrove ecosystem GPP not only be constrained by environmental factors, but also species composition and forest age structure can also be driving factors. The results of this study provide basic data to assess the contribution of regional mangrove forests to the global carbon cycle, and theoretical support to reveal the key environmental factors affecting mangrove ecosystem carbon dynamics.